A finite strain elastic-viscoplastic model of Gum Metal. (August 2019) - Kowalczyk-Gajewska, K.; Pieczyska, E.A.; Golasiński, K.; Maj, M.; Kuramoto, S.; Furuta, T.
Abstract: A hyperelastic-viscoplastic model of Gum Metal is presented. The model is formulated in the large strain framework. The free energy function is postulated consisting of the hyperelastic and viscoplastic components. Original extension of the Neo-Hooke model with a power law component is proposed for hyperelasticity, which enables to describe a relatively large non-linear elastic regime observed for the alloy. Viscoplastic strain follows the Perzyna-type law with an overstress function. The model is implemented into the finite element method and used to simulate the Gum Metal response in multiple tension loading-unloading cycles. The results are compared with experimental outcomes. Good accordance of the simulation results and the available experimental data is obtained. Highlights: Hyperelastic-viscoplastic model of Gum Metal is formulated. Extension of the Neo-Hooke model with a power law component is proposed. The model is implemented in the finite element method. Gum Metal response in multiple tension loading-unloading cycles is simulated. Good accordance with available experimental data is obtained.